Non-invasive diagnosis of hepatocellular carcinoma revisited - Müller, Cora; Waldburger, Nina; Stampfl, Ulrike; Kauczor, Hans-Ulrich; Schirmacher, Peter; Sommer, Christof-Matthias; Longerich, Thomas (Gut, 2018)
We read with interest the recent work by Ho et al demonstrating mutational hyperactivation of mammalian target of rapamycin signalling in a subgroup of hepatocellular carcinoma (HCC).1 As Berasain and Lechel concluded that the prospect of a positive therapeutic response may outweigh the risk associated with the HCC biopsy procedure2 and histology is essential for confirming a diagnosis of intrahepatic cholangiocarcinoma (ICC),3 we revisited the performance of non-invasive HCC diagnosis as recommended by current guidelines (eg, American Association for the Study of Liver Diseases (AASLD)) in clinical practice. 4 We retrospectively analysed all patients (n=182) in which a CT-guided liver biopsy was performed at a tertiary referral centre within a 9-year period due to the clinical differential diagnosis of HCC. After quality control, a total of 94 biopsies (figure 1A, see online supplementary table 1) could be evaluated. HCC development was associated with the presence of cirrhosis (n=51/65, p<0.001), which was also found in 27% (3/11) of ICC and 33% (1/3) of combined hepatocellular-cholangiocarcinoma (HCC-CC) patients. The number of false-positive non-invasive HCC diagnosis was higher in patients without cirrhosis (n=13/19; table …
Published online first: 12 september 2017
Gesehen am 06.05.2019